Pelatihan Pengajaran Bahasa Inggris Dengan Kombinasi “Vocabulary Chain” dan “Storytelling” di SMA PGRI Pekanbaru - Abbas, M. Fadhly Farhy; Herdi, Herdi; Derin, Tatum (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2025)
This community service activity is based on the problems and needs of English teachers at SMA PGRI Pekanbaru City. The problem is that many students hesitate to speak English because they are afraid of making mistakes due to lack of vocabulary. The main focus of this activity is to provide support for effective learning methods in building an English vocabulary arsenal in the classroom without having to burden students to memorize a number of new vocabularies, such as the typical way of teaching vocabulary that is often carried out in many schools in Pekanbaru City. For this reason, the implementing team considered it necessary to carry out community service to all English teachers and students at SMA PGRI Pekanbaru City in the form of socialization and short training on gamification of English teaching that combines the Vocabulary Chain game and Three-sentence Storytelling, and accompanied by discussions and questions and answers to the participants of the activity. As a result, from the interpretation of the findings through the pre-test and post-test questionnaires, it was found that the activity succeeded in opening the teachers' insights into the depth of the potential of the two games that had been carried out for a long time but had not been very effective in encouraging students to dare to speak up so far.